2019
DOI: 10.22159/ajpcr.2019.v12i3.30853
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of High-Performance Liquid Chromatographic Method for Determination of Dapagliflozin and Its Impurities in Tablet Dosage Form

Abstract: Objective: The aim of the present work is the development of new, sensitive, specific, and accurate high-performance liquid chromatographic method for the separation and determination of dapagliflozin and its impurities in tablet dosage form. Methods: The chromatographic separation of drug and its impurities was achieved using Hypersil BDS C18 column (250 mm × 4.6 mm, 5 μ) with mobile phase consisted of mobile phase-A (Buffer pH 6.5) and mobile phase-B (acetonitrile:water 90:10) by gradient program at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…The retention time of DPG was longer 22.965 minutes in the proposed method compared to the reported method. However, the proposed method in our study was found more sensitive (LOD of 8.59 ng/mL) with shorter runtime of 70 minutes than the reported one 14 . The proposed method also offers an advantage in determining the relationship between the impurity profile and the stability profile.…”
Section: Comparison With Reported Methodscontrasting
confidence: 67%
See 3 more Smart Citations
“…The retention time of DPG was longer 22.965 minutes in the proposed method compared to the reported method. However, the proposed method in our study was found more sensitive (LOD of 8.59 ng/mL) with shorter runtime of 70 minutes than the reported one 14 . The proposed method also offers an advantage in determining the relationship between the impurity profile and the stability profile.…”
Section: Comparison With Reported Methodscontrasting
confidence: 67%
“…The published HPLC-VIS method for the determination of DPG and its six impurities used different chromatographic conditions (mobile phase and detection wavelength) 14 . The retention time of DPG was 16.95 min, with a LOD of 0.065 µg/mL, a linearity range was 0.20-13.00 µg/mL, and a total runtime of 75 minutes.…”
Section: Comparison With Reported Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DAPA is a SGLT-2 inhibitor indicated for managing diabetes mellitus Type 2. When combined with diet and exercise in adults, DAPA helps to improve glycemic control by inhibiting glucose resorption in the proximal tubule of the nephron and causing glycosuria [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%